Antibiotic use among patients with febrile illness in a low malaria endemicity setting in Uganda. - Batwala, Vicent; Magnussen, Pascal; Nuwaha, Fred (BioMed Central Ltd, 2011)
Uganda embraced the World Health Organization guidelines that recommend a universal ‘test and treat’ strategy for malaria, mainly by use of rapid diagnostic test (RDT) and microscopy. However, little is known how increased parasitological diagnosis for malaria influences antibiotic treatment among patients with febrile illness.
Antibiotic use among patients
Keywords: : Antibiotic treatment, febrile patients, malaria diagnosis